2022
DOI: 10.3390/pharmaceutics14112359
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota-Derived Short-Chain Fatty Acids: New Road in Colorectal Cancer Therapy

Abstract: The colon microbiota is an important player in colorectal cancer (CRC) development, which is responsible for most of the cancer-related deaths worldwide. During carcinogenesis, the colon microbiota composition changes from a normobiosis profile to dysbiosis, interfering with the production of short-chain fatty acids (SCFAs). Each SCFA is known to play a role in several biological processes but, despite their reported individual effects, colon cells are exposed to these compounds simultaneously and the combined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…Despite being known that each SCFA plays a role in several biological processes, it is also important to understand the combined effects of the three SCFAs, since colon cells are exposed to these compounds simultaneously [ 44 ]. Recently, our group reported that all three SCFAs, alone or combined at the physiological proportions found in the human colon (60 acetate: 15 butyrate: 25 propionate), revealed to have a selective and anticancer effect by inhibiting colony formation and cell proliferation, increasing apoptosis, disturbing the energetic metabolism, inducing lysosomal membrane permeabilization, and decreasing cytosolic pH [ 44 ]. Additionally, this study showed for the first time that SCFAs are specific towards colon cancer cells, showing promising therapeutic effects [ 44 ].…”
Section: Short-chain Fatty Acids In the Human Colonmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite being known that each SCFA plays a role in several biological processes, it is also important to understand the combined effects of the three SCFAs, since colon cells are exposed to these compounds simultaneously [ 44 ]. Recently, our group reported that all three SCFAs, alone or combined at the physiological proportions found in the human colon (60 acetate: 15 butyrate: 25 propionate), revealed to have a selective and anticancer effect by inhibiting colony formation and cell proliferation, increasing apoptosis, disturbing the energetic metabolism, inducing lysosomal membrane permeabilization, and decreasing cytosolic pH [ 44 ]. Additionally, this study showed for the first time that SCFAs are specific towards colon cancer cells, showing promising therapeutic effects [ 44 ].…”
Section: Short-chain Fatty Acids In the Human Colonmentioning
confidence: 99%
“…Recently, our group reported that all three SCFAs, alone or combined at the physiological proportions found in the human colon (60 acetate: 15 butyrate: 25 propionate), revealed to have a selective and anticancer effect by inhibiting colony formation and cell proliferation, increasing apoptosis, disturbing the energetic metabolism, inducing lysosomal membrane permeabilization, and decreasing cytosolic pH [ 44 ]. Additionally, this study showed for the first time that SCFAs are specific towards colon cancer cells, showing promising therapeutic effects [ 44 ]. All the current evidence concerning the effects of acetate, butyrate, and propionate on CRC cells, alone or in combination, clearly supports the potential use of SCFAs in cancer prevention and treatment [ 2 ].…”
Section: Short-chain Fatty Acids In the Human Colonmentioning
confidence: 99%
“…Despite the advances in CRC treatment options, classical chemotherapy with 5-Fluorouracil (5-FU) is still a clinical problem due to resistance, presenting response rates of less than 10% in metastatic CRC patients [2]. The intestinal microbiota, composed of a large population of microorganisms modulated by dietary patterns, has been increasingly linked with CRC [3,4]. Differences in intestinal microbiota composition have been reported between patients with CRC and healthy individuals, and the reduced production of microbiota-derived short-chain fatty acids (SCFAs), namely acetate, butyrate, and propionate, is linked to a high CRC risk [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…However, the effectiveness of this approach would likely vary according to individual intestinal flora and dietary compliance. In the search for new alternatives for CRC treatment capable of overcoming some of the limitations associated with the currently available approaches in the clinic, SCFA administration has been also been considered [3,7,8,[10][11][12]. This possibility was advanced due to their described role in several biological processes against CRC cells [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation